Nietzsche’s Society - Wells, Kristen (Stance: an international undergraduate philosophy journal, 2013)
This essay asserts that Nietzsche proposes an important role for society within his ethics, and that this societal aspect has been greatly overlooked by Nietzsche scholars. By identifying a soul-state analogy and resemblance to virtue ethics, this essay contends that Nietzsche intends for societies and individuals to be seen as complementary parts of the will to power. Like Aristotle, Nietzsche prescribes an ideal society essential to greatness. By recognizing the importance of the role of society in Nietzsche’s philosophy, Nietzsche scholarship is better positioned to consider new applications of his philosophical principles with his goals in mind.